Childhood Maltreatment and Somatic Symptoms in Adulthood: Establishing a New Research Pathway - Lüönd, Antonia M. (2025)
Background: Somatic symptoms, such as chronic pain, fatigue, and gastrointestinal disturbances, are commonly reported in individuals with a history of childhood maltreatment (CM), which includes various forms of abuse and neglect experienced before age 18. Although CM is strongly associated with somatic symptoms, the specific relationships between CM subtypes and these symptoms, as well as the mechanisms connecting them, remain insufficiently understood. This review examines the complex interaction between CM and somatic symptoms, which often coexist with mental disorders and significantly impact quality of life and healthcare systems. Summary: Somatic symptoms, frequently a mix of "explained" and "unexplained" conditions, are associated with personal distress and pose diagnostic challenges. CM has been linked to these symptoms through neurobiological mechanisms, such as HPA axis dysregulation and allostatic load, while theoretical models emphasize the roles of hyperawareness, cultural factors, and vulnerability in symptom development. However, existing research often fails to account for specific CM subtypes, the full range of somatic symptoms, and cultural and situational factors, leading to inconsistencies in findings. Key messages: Bridging gaps in literature requires adopting the World Health Organization's CM subtype definitions and ICD-11 codes (MA00-MH2Y) to encompass a broader spectrum of somatic symptoms. Employing rigorous methodologies, such as systematic reviews and meta-analyses, is essential for advancing understanding. These approaches can enhance diagnostic accuracy, support tailored interventions, and promote a biopsychosocial framework for CM research, ultimately improving patient outcomes and alleviating societal burdens.